2007
DOI: 10.1177/0363546507300260
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Profile of Hip Rotation Range of Motion in Elite Tennis Players and Professional Baseball Pitchers

Abstract: This study established typical range of motion patterns and identified bilaterally symmetric hip active range of motion rotation values in elite tennis players and professional baseball pitchers. Asymmetric hip joint rotational active range of motion encountered during clinical examination and screening may indicate abnormalities and would indicate the application of flexibility training, rehabilitation, and further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 23 publications
7
81
2
5
Order By: Relevance
“…Furthermore, active hip internal and external rotation ROMs on the dominant side were also found to be greater in this study (internal rotation: 33.3-38.98 and external rotation: 41.1-46.68) compared with those reported by Ellenbecker et al (5) (internal rotation: 238 and external rotation: 348) among professional baseball players. The differences observed in the hip rotation ROM values between both the studies could be sport specific or most likely be attributed to methodological dissimilarities between studies, e.g., seated in this study vs. prone in the study by Ellenbecker et al (5).…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, active hip internal and external rotation ROMs on the dominant side were also found to be greater in this study (internal rotation: 33.3-38.98 and external rotation: 41.1-46.68) compared with those reported by Ellenbecker et al (5) (internal rotation: 238 and external rotation: 348) among professional baseball players. The differences observed in the hip rotation ROM values between both the studies could be sport specific or most likely be attributed to methodological dissimilarities between studies, e.g., seated in this study vs. prone in the study by Ellenbecker et al (5).…”
Section: Discussionmentioning
confidence: 60%
“…[22][23][24][25] It also allowed us to quantify a potential dose-effect relation between exposure to the ICU and severity of limitation in the range of motion. In addition, we defined "functionally significant contracture" as more severe limitation in the range of motion, to an extent that has been established in the literature as causing functional limitation 8,17,19,21,26 (Table 1).…”
Section: -21mentioning
confidence: 99%
“…Results suggest a sex difference where women players had significantly higher values for hip internal rotation, SLR and HBD items compared to men. Since previous studies have reported that healthy women in the general population have high values for hip internal rotation and SLR angle (Okabe et al, 1980;Idota & Yoshida, 1991), top level Japanese women track athletes have higher values for hip internal rotation and SLR angle and lower values for HBD compared to men (Takahashi et al, 2012), and elite women tennis players have higher values for hip internal rotation compared to men (Ellenbecker et al, 2007), we assume that greater range of motion and flexibility among women compared to men for hip internal rotation, SLR and HBD items is a sex difference as opposed to an attribute of the sport.…”
Section: Discussionmentioning
confidence: 99%